Ornithodoros guaporensis (Acari, Ixodida: Argasidae), a new tick species from the Guaporé River Basin in the Bolivian Amazon - Venzal, Santiago Nava, José M.; Terassini, Flavio A.; Mangold, Atilio J.; Camargo, Luis M. A.; Casás, Gustavo; Labruna, Marcelo B. (Zootaxa, 2013)
The soft tick Ornithodoros guaporensis n. sp. (Acari: Ixodida: Argasidae) is described from larvae and adults. Morpho-logical analysis and 16S rDNA sequences are provided. Adults were collected from a rocky fissure inhabited by bats lo-cated in the Amazonian forest in north-eastern Bolivia (Beni Department) close to the Guaporé River. Larvae were obtained from eggs laid by females collected in the field, and which were fed on rabbits in the laboratory. Larvae of O. guaporensis are morphologically closely related to Ornithodoros rioplatensis, Ornithodoros puertoricensis and Orni-thodoros talaje. Larvae of O. guaporensis and O. rioplatensis can be separated from O. puertoricensis and O. talaje by the number of pairs of dorsal setae (20 in O. guaporensis and O. rioplatensis, 18 in O. puertoricensis and 17 in O. talaje). Larvae of O. guaporensis and O. rioplatensis can be differentiated by the medial dental formula (2/2 in O. guaporensis and 3/3 in O. rioplatensis) and the apex of the hypostome, which is more pointed in O. rioplatensis than in O. guaporensis. The Principal Component Analysis performed with morphometric characters of larvae showed a clear separation among O. guaporensis, O. rioplatensis, O. puertoricensis and O. talaje. Significant morphological differences among adults of these four species were not found. The analysis of the 16S rDNA sequences allowed for the differentiation between O. guaporensis and the remaining Neotropical species of the family Argasidae.